Enhancing MSME marketing through creative digital content development in Bondowoso, Indonesia - Putra, Dhony Manggala; Hakim, Lukman; Mukhlisoh, Nanik Anita; Suparto, Suparto; Afriansyah, Faisal Lutfi; Efendi, Rizky Kurniawan; Putri, Marsheila Karisa; Avriza, Ariel Henry; Fitriani, Rinfani Dwi (P3M Politeknik Negeri Jember, 2025)
This study addresses the challenges faced by four food-based Micro, Small, and Medium Enterprises (MSMEs) in Bondowoso, Indonesia—namely Ila Snack Bondowoso, Rien’s Kitchen, Tahu Sutrisno, and Kripik Ayu—in developing effective digital marketing content. Limited digital skills and resources hinder their ability to promote their products and reach broader audiences. To address this, the research employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to create high-quality promotional videos tailored to the needs of these MSMEs. These videos, featuring company profiles and product highlights, were crafted using professional-grade tools and enhanced with voiceovers to meet industry standards. The videos adhered to the AIDA (Attention, Interest, Desire, Action) model, ensuring effective audience engagement and action-driven messaging. Expert validation and field testing confirmed their effectiveness, while consumer feedback indicated a positive impact on purchasing decisions. This research highlights the potential of creative digital content to empower MSMEs, enhance product visibility, and strengthen market competitiveness. The findings provide a replicable framework for supporting small enterprises globally, underscoring the critical role of digital innovation in driving inclusive economic growth and cultural preservation.